Harmonisasi syariat dan praktik bisnis: Penerapan akad salam pada usaha katering - chaniago, ikwal pangsa (Maliki Interdisciplinary Journal, 2026)
The Salam sale and purchase contract is a crucial instrument in Islamic jurisprudence (fiqh) of muamalah (Islamic transactions). It is characterized by advance payment and delivery of goods at an agreed time, emphasizing the principles of fairness, clarity, and legal certainty. Discussions on the Salam contract have traditionally focused on the agribusiness sector, while its application in the food service industry, such as catering, has rarely been comprehensively studied. Yet, the food ordering system in catering has characteristics nearly identical to the Salam contract, particularly regarding the clarity of the menu, quantity, price, and delivery time. This article aims to explain the legal basis, pillars, and requirements of the Salam contract, while also examining its relevance to modern catering practices. The study's findings indicate that the implementation of the Salam contract in catering is not only valid according to Sharia law but also provides mutual benefit, transparency, and opportunities for economic empowerment of the community. These findings provide a new contribution to the literature on Islamic economics by confirming that the Salam contract can be adapted to the modern service sector, including through the development of digital ordering systems.